Self-Reliant Community Development in a Semi-Urban Area of Bangkok: A Case Study of Community Well-Being - Thaithae, Suparp; Chiangkhong, Araya; Thanaboonpuang, Parinyaporn (The Journal of Behavioral Science, 2021)
Developing self-reliance in community plays an important role to enhance the well-being and participation of its members. This study aimed to understand the conditions which contribute to the success of community well-being and the strategies to develop healthy communities. Qualitative research methodology was employed. The data collection strategy utilized in-depth interviews of thirteen key informants from the core group leaders and local residents of the community and from community development networks in Bangkok, Thailand. Data analysis was conducted through content analysis methods. The results showed that two conditions contributed to the success in community well-being. Firstly, it included human potential capital such as having outstanding leadership capabilities, for example, being patient, team oriented, well respected, and the potential of the elder leader’s core group in contributing their experience. Secondly it included the ability to foster community development; cultural capital, namely, having a traditional community with close family ties; and natural resource capital with some plants as an economic crop. In addition, the community need to collaborate with network partners. Those strategies in implementing community well-being operations included, 1) fostering community participation in a “healthy space”; 2) creating exposure to a wide range of organizational networks; 3) the implementation of a mentoring system; and 4) continuous development of the “healthy space” and opening it for public use, along with fostering cooperation with neighboring communities. Practical implications for sustainable development in the area of community well-being are discussed.